Determination of flavor‐potentiating compounds in different Italian tomato varieties. Issue 5 (18th April 2021) - Tommonaro, Giuseppina; Morelli, Carlo F.; Rabuffetti, Marco; Nicolaus, Barbara; De Prisco, Rocco; Iodice, Carmine; Speranza, Giovanna
Abstract: Umami taste, known as appetizing sensation, is mainly imparted by monosodium glutamate (MSG, the first identified umami factor) in synergistic combination with some 5′ ribonucleotides such as inosine 5′‐monophosphate, IMP, guanosine 5′‐monophosphate, GMP, and adenosine 5′‐monophoshate, AMP. The level of free glutamic acid in tomatoes is higher than in other vegetables or fruits and increases with ripening and industrial processing. In addition, due to the presence of bioactive metabolites, tomatoes and tomato‐based products are among the most consumed healthy food items. The levels of the major umami compounds of tomato, that is, glutamate and 5′‐ribonucleotides (GMP and AMP) were assessed in different parts (skin, outer flesh, and inner pulp) of known tomato varieties from southern Italy: San Marzano Originale, San Marzano 245, Black Tomato, Corbarino Corbara, Corbarino Nocera, and Superpomodoro (tomato hybrid). Such varieties were also investigated for their antioxidant properties through DMPD, DPPH, and ABTS assays, with San Marzano Originale showing the highest antioxidant power both in lipophilic and methanolic fractions. The concentration of umami compounds in tomato differs with the part of the fruit analyzed and is greatly dependent on the variety, being Corbarino Nocera the cultivar richest in glutamate and Superpomodoro in ribonucleotides. As for nutritional aspect, results confirm the great nutraceutical feature of San Marzano tomato, the most known variety used in industrial processes. Practical applications: This study was planned to develop a method to quantify the major umami compounds that strongly influence the organoleptic properties of many different tomato varieties. It is known that the sensory quality of fruits and vegetables is an important factor in consumer's choice. The analytical methods described here enabled the evaluation of the glutamate and 5′‐ribonucleotides contents in six selected varieties of tomato from Campania region, and can be easily used to determine the sensory profile of commercial varieties, for example, those perceived as not very tasteful by consumers. Abstract : The levels of the major umami compounds of tomato, that is, glutamate and 5′‐ribonucleotides (GMP and AMP) were assessed in different parts (skin, outer flesh, and inner pulp) of known tomato varieties from southern Italy. San Marzano Originale showing the highest antioxidant power both in lipophilic and methanolic fractions. The concentration of umami compounds in tomato differs with the part of the fruit analyzed and is greatly dependent on the variety.